Pengaruh Tugas Kesenjangan Pendapat, Penalaran, dan Informasi terhadap Keterampilan Berbicara - Sri Mulyani; Vismaia S. Damaianti; Yeti Mulyati; Andoyo Sastromiharjo (Universitas Mulawarman, 2023)
The purpose of this study was to test the effectiveness of applying the three gap tasks, namely the gaps of reasoning, opinion, and information in improving middle-level students' speaking skills. The research method used in this research is quasi-experimental. The research participants totaled 200 students who were divided into two groups, namely experimental and control. Participants were divided into three experimental groups and one control group. The students' initial ability in each group was tested to ensure that the students' initial speaking ability did not differ much. The treatment of the three gap assignments was given to the experimental group. The results showed that the three experimental groups that received the intervention for gaps in reasoning, opinions, and information experienced a more significant increase in their speaking ability than the control group. Improvement of students' speaking skills can be seen from various aspects both verbally and nonverbally. It can be concluded that these three gaps of opinion, reasoning, and information tasks are more effective than traditional methods in improving students' speaking skills. The implication of the research is that teachers can choose these three gap tasks to train students in speaking as well as organize their talk.